A Novel Framework Using Structured Robustness Score in Keyword Quries Over Database by Feedback Algorithm and Profile Migration Scheme - Sivaranjani, K; Geetha, V (International Journal of Computer Sciences and Engineering, 2025)
Magic word questions on data bases offer simple accessibility to data, however for the most part endure from low positioning quality, i.e., low exactitude and/at that point again recall, as demonstrated in recent benchmarks. It’d be accommodating to spot questions that square measure presumably to own low positioning quality to make strides the customer satisfaction. at that point again example, the framework could recommend to the customer diverse questions at that point again such onerous queries.. We set forth a high-principled framework and proposed novel calculations to live the degree of the issue of a question over a dB, exploitation the positioning strength principle. Supported our framework, we tend to proposture novel calculations that with proficiency anticipate the adequacy of a magic word question. Our intensive tests show that the calculations anticipate the issue of a question with comparatively low errors and negligible time overheads.